Dekonstruksi Pasal-pasal Kontra Produktif dalam Undang-undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Mahir, Mahir; Saoki, Saoki (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence is the state's effort to provide legal protection for women victims of sexual violence. However, along the way, several articles were found that were counter-productive, which were allegedly the entry point for the rise in cases of sexual violence occurring amidst strict legal regulations. Departing from this, this article attempts to provide a study regarding the existence of counter-productive articles, ideal deconstruction and policy direction for law enforcement related to these articles. The results of this research are: (1) it was found that several articles were counter-productive because they were considered to be overcriminalization, had the wrong object, were not followed up with implementing regulations, and determined the sentence incorrectly because it was contrary to the principles of punishment; (2) deconstruction of counter-productive articles can be carried out through revision of the normative formulation of these articles and the formulation of more comprehensive implementing provisions; and (3) Law Number 12 of 2022 is directed as the ultimate legal instrument in enforcing the law on criminal acts of sexual violence through preventive and repressive regulations.